(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
A total of 72 rice genotypes including Balam (40), Jesso-Balam (27) rice land races and popular varieties (5) from Bangladesh were characterized using 45 SSR markers for studying genetic diversity and identification of duplicate germplasm. Altogether 430 alleles were detected which varied from 4 to 18 per locus with an average of 9.6. The highest number of alleles (18) was found in the locus RM302. The highest gene diversity (0.91) was found in RM337 and RM224, while the lowest (0.52) was found in RM237. The PIC values ranged from 0.90 to 0.46 with an average of 0.78. The highest PIC value was observed in loci RM337 and RM224 followed by 0.89 in RM55, RM258, RM21 and RM206, respectively. The gene diversity and PIC values revealed that RM337, RM224, RM55, RM258, RM21 and RM206 were the best markers to identify and distinguish the genotypes. Besides, the UPGMA clustering method generated seven clusters, where no duplicate genotype was found. It also showed that Balam and Jesso-Balam groups of germplasm were constellated into separate clusters. The Neis genetic distance ranged from 0.3556 to 1.0. Conserved, characterization and utilization of the unique and distinct variability of all the similar or duplicate named land races of Balam and Jesso-Balam rice is suggested.